Localized sclerostin accumulation in osteocyte lacunar-canalicular system is associated with cortical bone microstructural alterations and bone fragility in db/db male mice - Wu, Xingfan; Ai, Yuanli; He, Yutao; Ma, Dan; Li, Xi; Huang, Xiao; Cheng, Rui; Wang, Bin (Frontiers in Cell and Developmental Biology, 2025)
Bone fragility in type 2 diabetes mellitus (T2DM) is often characterized by impaired bone quality, despite normal or increased bone mineral density. Serum sclerostin levels are elevated in diabetes, yet its role in bone fragility is not fully understood. Sclerostin (SOST) is a Wnt signaling inhibitor primarily secreted by osteocytes, regulating bone formation and homeostasis. Sclerostin inhibits Wnt signaling, suppressing osteoblast differentiation and activity, which limits bone formation. However, the localized effects of sclerostin within the osteocyte lacunar-canalicular system (LCS) and its contribution to bone fragility in T2DM remain unclear. In this study, we investigated the role of elevated sclerostin in bone fragility using the db/db mice. We found that db/db mice exhibited significant osteoporosis, increased bone fragility, and structural damage to the LCS. Sclerostin expression was elevated, and its accumulation within the cortical bone LCS correlated with increased expression of matrix-degrading enzymes, including Cathepsin K (CTSK) and matrix metalloproteinase 13 (MMP-13). Further in vitro experiments with recombinant sclerostin confirmed the upregulation of these enzymes, suggesting that sclerostin’s local effects within the LCS contribute to matrix degradation. These preliminary findings indicate that localized sclerostin accumulation in LCS is associated with cortical bone microstructural alterations and fragility in db/db male mice. This study highlights the potential of targeting sclerostin’s local effects within the LCS as a therapeutic strategy to prevent bone deterioration in diabetes.